The China model : political meritocracy and the limits of democracy - Bell, Daniel (Daniel A.), 1964- (Princeton, New Jersey : Princeton University Press, 2015)
"Westerners tend to divide the political world into 'good' democracies and 'bad' authoritarian regimes. But the Chinese political model does not fit neatly in either category. Over the past three decades, China has evolved into a political system that can best be described as 'political meritocracy.' [This work] seeks to understand the ideals and the reality of this unique political system"--
Includes bibliographical references (pages [199]-305) and index.
Keywords: Political culture -- China; Merit (Ethics) -- Political aspects -- China; Political leadership -- China; Elite (Social sciences) -- Political activity -- China; Democracy -- China; China -- Politics and government -- 1976-2002.; China -- Politics and government -- 2002-